Identification of novel immune cell signature in gastroesophageal reflux disease: altered mucosal mast cells and dendritic cell profile - Ustaoglu, Ahsen; Daudali, Fatema Arif; D’afflitto, Manfredi; Murtough, Stephen; Lee, Chung; Moreno, Estefania; Blaydon, Diana C.; Kelsell, David P.; Sifrim, Daniel; Woodland, Philip; Peiris, Madusha (Frontiers in Immunology, 2023)
Heartburn pathogenesis in GERD remains incompletely understood. We aimed to identify differences in the immune cell signature and sensory mucosal markers between reflux phenotypes and healthy asymptomatic subjects. Thirty-seven patients with heartburn symptoms were phenotyped endoscopically and with objective reflux studies into erosive reflux disease (ERD)(N=10), nonerosive reflux disease (NERD)(N=9), functional heartburn (FH)(N=9), and Barrett's esophagus (BO)(N=9).Bulk mRNA-sequencing(RNA-seq) was conducted on RNA extracted from endoscopic biopsies, and immune cell deconvolution analysis was performed using CIBERSORT. RNA-seq findings were validated by immunofluorescent staining for CD1a, nerve growth factor(NGF), and mast cell tryptase in corresponding patient biopsies. Transcriptomic analysis detected higher mast cell abundance in BO, ERD, and NERD compared to healthy controls(p<0.05), with decreased dendritic cell infiltration in BO, ERD, and NERD patients compared to healthy controls and FH patients. CD1a-positive dendritic This is a provisional file, not the final typeset article cell infiltration was significantly higher in the healthy esophageal mucosa at protein level compared to BO(p=0.0005), ERD(p=0.0004), and FH patients(p=0.0096). Moreover, NGF co-expression on mast cells in GERD patients was significantly higher than in healthy controls(p=0.0094). In conclusion, the mucosa in patients with GERD had a significant increase in NGF expression on mast cells, suggesting an upregulation of signalling for neuronal sprouting in GERD. Moreover, decreased dendritic cell abundance in GERD esophageal mucosa may play a role in reduced oral tolerance and development of subsequent immune responses which may participate in esophageal sensitivity.